Molecular features of bile salt hydrolases and relevance in human health - Chand, D.; Avinash, V. S.; Yadav, Y.; Pundle, A. V.; Suresh, C. G.; Ramasamy, S. (Biochimica et Biophysica Acta - General Subjects, 2017)
Background: Bile salt hydrolase (BSH) enzyme is responsible for the de-conjugation of bile salts by commensal bacteria, thus playing a vital role in their colonization and survival in the mammalian intestine and determination of their probiotic potential. Further, bile deconjugation also leads to lowering of cholesterol and alterations in energy homeostasis, thus making BSH a clinically important enzyme. Scope of the review: Many recent observations have indicated that BSH may be involved in a multifaceted array of roles, directly or indirectly in the host and microbial physiology. BSH paralogues have now been found to occur in different microbes including free-living and pathogenic bacteria and Archaea. BSHs from various sources also show differential activity and substrate spectrum. Certain bacteria are known to possess multiple genes for BSH enzymes. BSHs have been reported to influence different metabolic phenomena, including bacterial pathogenesis and the maintenance of lipid and glucose homeostasis in the host. These observations necessitate an intense study into the biochemical, structural and regulatory features of BSH enzymes to better understand their role in regulating bacterial and host metabolism. Major conclusions: In this review, the available information on the characteristics of BSH enzymes have been organized in order to understand their interactions with a wide range of substrates and their myriad physiological roles, from bile resistance to signalling mechanisms. General significance: A detailed exploration of BSH architecture and regulation could provide insights into its evolution and a deeper appreciation of the multiple functions of this enzyme relevant to healthcare.